SURVEY ON VIRTUAL LOAD BALANCING ARCHITECTURES IN MOBILE CLOUD - Pandian, M. Durai (IRO Journal on Sustainable Wireless Systems, 2019)
The mobile cloud computing, that enables the mobile device application to be hosted, equipped and constructed by the cloud-computing has become more prominent among wide range of application and the concerns that range either in the smallscale or the large-scale. This lead to the overcrowded accessing of the mobile clouds which lead to insufficiency of resources and the latency in the service provisioning. The possible researches emerged with the solutions of load balancing, but the in capabilities in the traditional load balancing developed were in compatible with the mobile cloud computing. So the paper details the survey on the virtual load balancing techniques available and their employment in the mobile cloud computing to improve the balancing of the influx traffic that are addressed towards the mobile cloud computing.